2014
DOI: 10.1007/s00715-014-0335-4
|View full text |Cite
|
Sign up to set email alerts
|

Klinischer Effekt biomimetischer Mineralisation bei Approximalkaries

Abstract: Zusammenfassung Hintergrund Karies hat bis heute eine hohe Prävalenz, auch in westlichen Ländern mit präventiven zahnmedizinischen Angeboten. Bei mechanischer Therapie werden die behandelten Zähne geschwächt. Dies führt über die Jahre oder Jahrzehnte häufig zum Verlust mit erheblichen Folgekosten. In den letzten Jahren eingeführte remineralisierende Substanzen sollen die etablierten remineralisationsfördernden Fluoride ergänzen. Daneben stehen die nicht oder minimal-invasiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…A “natural” repair process, such as a regenerative treatment of caries, which does not rely upon the patient's compliance, is becoming a focus in dentistry . P 11 ‐4 has been described as a biomimetic mineralization agent, and has shown promising results in in vitro and in vivo studies . P 11 ‐4 assembles to form hierarchical 3‐D fibrillar networks under physiological conditions, such as what would be anticipated within caries lesions .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A “natural” repair process, such as a regenerative treatment of caries, which does not rely upon the patient's compliance, is becoming a focus in dentistry . P 11 ‐4 has been described as a biomimetic mineralization agent, and has shown promising results in in vitro and in vivo studies . P 11 ‐4 assembles to form hierarchical 3‐D fibrillar networks under physiological conditions, such as what would be anticipated within caries lesions .…”
Section: Discussionmentioning
confidence: 99%
“…It is able to regenerate mineral for enamel repair using a process that is analogous to the enamel matrix during enamel formation . In previous studies, P 11 ‐4 was shown to promote subsurface mineralization in the presence of saliva both in vitro and in vivo . Recently, it was shown by ultrasonic assessment and scanning electron microscopy (SEM) that the treatment of demineralized enamel surfaces with P 11 ‐4 could inhibit demineralization and facilitate hydroxyapatite crystal formation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low viscosity isotropic P11-4 when applied on the initial carious lesion rapidly diffuses into the lesion body, where it transforms to an elastomeric nematic gel in the presence of cations and pH < 7.4, leading to the 3-dimensional fibre matrix assembly and subsequent biomineralization of the lesion [Brunton et al, 2013]. The P11-4-treated carious lesions showed a significantly improved visual appearance and increased radiographic opacity, remaining stable even 6-12 months after treatment [Schlee et al, 2014[Schlee et al, , 2018. A recent randomized controlled trial (RCT) demonstrated that biomineralization facilitated by P11-4 in combination with fluoride is safe and more effective than the present clinical gold standard of fluoride treatment alone [Alkilzy et al, 2018b].…”
Section: Biomimetic Remineralizationmentioning
confidence: 98%
“…This includes the ability to reverse early occlusal and proximal lesions that are more resistant to fluoride remineralization than smooth surface lesions [Alkilzy et al, 2018a[Alkilzy et al, , 2015Brunton et al, 2013;Schlee et al, 2014Schlee et al, , 2018. The low viscosity isotropic P11-4 when applied on the initial carious lesion rapidly diffuses into the lesion body, where it transforms to an elastomeric nematic gel in the presence of cations and pH < 7.4, leading to the 3-dimensional fibre matrix assembly and subsequent biomineralization of the lesion [Brunton et al, 2013].…”
Section: Biomimetic Remineralizationmentioning
confidence: 99%